FE Modeling of Circular, Elliptic, and Triangular Isolated Slabs With a Continuous Damage Model - Juárez-Luna, Gelacio; Caballero-Garatachea, Omar (Frontiers in Built Environment, 2019)
The nonlinear behaviour of reinforced concrete circular, elliptic and triangular isolated slabs was studied using computational mechanics. Concrete was modelled with a damage model which includes softening, while the behaviour of the reinforcing steel was modelled with a 1D bilinear plasticity model. The constitutive models and the finite element method were validated by comparing the computed numerical results with the experimental results of a rectangular slab reported in the scientific literature. The coefficient method is proposed for its simplicity to calculate design bending moments in slabs with circular, elliptic and triangular geometries. These coefficients were computed from the FE analysis. The layout of steel reinforcement is proposed, particularly lengths of zones for positive and negative moments, respectively. The crack paths are showed, which are depending on the boundary conditions, acting loads and geometry of the slabs.